(untitled) (Revista da Faculdade de Odontologia - UPF, 2014)
Objective: to evaluate the additional antibacterial action of high-power diode laser after the use of 2.5% sodium hypochlorite and 2% chlorhexidine gel in root canals infected with E.faecalis. Materials and Method: 120 human teeth with single canal were inoculated with E.faecalis for 14 days and randomly divided into six groups (n=20), according to the chemical auxiliary substance used in the chemo-mechanical preparation and the use of high-power diode laser: G1(NaOCl) – root canal preparation with 2.5% sodium hypochlorite; G2(CHX) – root canal preparation with 2% chlorhexidine gel; G3(NaOCl+DL) - root canal preparation with 2.5% sodium hypochlorite+diode laser; G4(CHX+DL) - root canal preparation with 2% chlorhexidine gel+diode laser; G5(NaCl+DL) - root canal preparation with 0.9% saline solution+diode laser; G6(no treatment) – no treatment was performed. Microbiological test (CFUs counting) was performed to evaluate the effectiveness of proposed treatments. Data were subjected to One-way ANOVA followed by post-hoc Tukey test (Î±=0.05). Results: G3(NaOCl+DL) had reduction of 99.42% of E.faecalis, followed by G4(CHX+DL) – 93.48%; G1(NaOCl) – 89.82%; G2(CHX) – 81.86%; G5(NaCl+DL) – 65.40%; and G6(no treatment) – no reduction. There was significant statistical difference in CFUs of all groups in relation to G6(no treatment) (p